Implicit Processing of Pitch in Postlingually Deafened Cochlear Implant Users - Tillmann, Barbara; Poulin-Charronnat, Bénédicte; Gaudrain, Etienne; Akhoun, Idrick; Delbé, Charles; Truy, Eric; Collet, Lionel (Frontiers in Psychology, 2019)
Cochlear implant (CI) users can only access limited pitch information through their device, which hinders music appreciation. Poor music perception may not only be due to CI technical limitations; lack of training or negative attitudes towards the electric sound might also contribute to it. Our study investigated with an implicit (indirect) investigation method whether poorly-transmitted pitch information, presented as musical chords, can activate listeners’ knowledge about musical structures acquired prior to deafness. Seven postlingually deafened adult CI users participated in a musical priming paradigm investigating pitch processing without explicit judgments. Sequences made of eight sung-chords that ended on either a musically related (expected) target chord or a less-related (less-expected) target chord were presented. The use of a priming task based on linguistic features allowed CI patients to perform fast judgments on target chords in the sung music. If listeners’ musical knowledge is activated and allows for tonal expectations (as in normal-hearing listeners), faster response times were expected for related targets than less-related targets. However, if the pitch percept is too different and does not activate musical knowledge acquired prior to deafness, storing pitch information in a short-term memory buffer predicts the opposite pattern. If transmitted pitch information is too poor, no difference in response times should be observed. Results showed that CI patients were able to perform the linguistic task on the sung chords, but correct response times indicated sensory priming, with faster response times observed for the less-related targets: CI patients processed at least some of the pitch information of the musical sequences, which was stored in an auditory short-term memory and influenced chord processing. This finding suggests that the signal transmitted via electric hearing led to a pitch percept that was too different from that based on acoustic hearing, so that it did not automatically activate listeners’ previously acquired musical structure knowledge. However, the transmitted signal seems sufficiently informative to lead to sensory priming. These findings are encouraging for the development of pitch-related training programs for CI patients, despite the current technological limitations of the CI coding.